SELEKSI JAMUR RIZOSFIR NON-PATOGENIK UNTUK PENGENDALIAN PENYAKIT LAYU FUSARIUM PADA TANAMAN JAHE DI BENGKULU - Bambang Purnomo (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Biological control for improving the soil more supressive to pathogen can be regarded as save method to controling ginger wilt diseases. A number of fungi are potentially recognized to have capability to suppress the development of Fusarium wilt. The obyectives of this study were to select non-pathogenic fungi at the rhizosphere and to examine their isolates in suppressing the development of fusarium wilt disease in ginger. Fusarium oxysporum and non-pathogenic fungi were isolated from soil samples obtained from ginger production area which are endemic to the disease. The research involved exploration, fungi selection, and evaluation in a sucrose agar medium and ginger plant. The evaluation on ginger rhizosphere could isolate 19 species of non- pathogenic fungi, but only 12 isolates showed their capability to suppress fusarium growth. Pot evaluation of ginger plant demontrated that only 4 species were the most potential fungi as the controlling agent. The four species that are Trichoderma piluliferum, Gliocladium solani, Aspergillus oryzae, and Trichoderma viride. For further utilization of these species an effective and efficient carrier medium should be determined